Non-native Speech Learning in Older Adults - Ingvalson, Erin M.; Nowicki, Casandra; Zong, Audrey; Wong, Patrick C. M. (Frontiers in Psychology, 2017)
Though there is an extensive literature investigating the ability of younger adults to learn non-native phonology, including investigations into individual differences in younger adults’ lexical tone learning, very little is known about older adults’ ability to learn non-native phonology, including lexical tone. There are several reasons to suspect that older adults would use different learning mechanisms when learning lexical tone than younger adults, including poorer perception of dynamic pitch, greater reliance on working memory capacity in second language learning, and poorer category learning in older adulthood. The present study examined the relationships among older adults’ baseline sensitivity for pitch patterns, working memory capacity, and declarative memory capacity with their ability to learn to associate tone with lexical meaning. In older adults, baseline pitch pattern sensitivity was not associated with generalization performance. Rather, older adults’ learning performance was best predicted by declarative memory capacity. These data suggest that training paradigms will need to be modified to optimize older adults’ non-native speech sound learning success.